PENGARUH BEAUTY VLOGGER DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH PADA MASYARAKAT KINALI - Eko Putra (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the effect ofbeauty vlogger and celebrity endorser on purchasing decisions of Wardah cosmetic products in Kinali society. The number of samples in this study were 96 people. Based on the results of the study, there is an insignificant effect between beauty vloggers on purchasing decisions, as evidenced by the Tvaluearithmetic of 1.455 with a significant value of 0.149 > 0.05. Celebrity endorsers have a significant effect on purchasing decisions, the value of Tcount is 3.644 and a significant value is 0.000